Empowering Learners in Inland Water: The Development of Digital Textbooks Embedded with HOTs and Google is Informative - Nuryuliani, Dwi; Handoyo, Budi; Wijayanto, Bayu (Future Space: Studies in Geo-Education, 2024)
Digital textbooks have become indispensable tools in contemporary pedagogical paradigms, offering nuanced instructional material to learners. As we navigate the 21st century, students are mandated to demonstrate advanced competencies; however, a concerning 65% of students from National High Schools grapple with High Order Thinking Skills (HOTS) questions. In response to this discernible gap, this study introduces a digital textbook dedicated to inland water content, constructed around HOTS and synergistically integrated with Google services. The research and development process adopted the rigorous ADDIE model framework. Expert evaluations yielded encouraging results: material validation stood at 90%, linguistic validation at 90%, and media expert validation at 99%. Pilot trials at Malang National High School and MAN 7 Jombang recorded student approval ratings of 91%, while educator feedback was 85%. HOTS testing results ranged from medium to exceptionally high, with average scores of 84.5 at Malang National High School and 85.2 at MAN 7 Jombang. Cumulatively, the data underscores the suitability and potential efficacy of the proposed digital textbook in enhancing geographical education.